A psychometric evaluation of the Indonesian version of the collaborative practice assessment tool (CPAT) for assessing interprofessional education and collaborative practice among health practitioners and students - Ardyansyah, Bau D.; Cordier, Reinie; Brewer, Margo; Parsons, Dave (Narra J, 2024)
Research focus has transitioned from interprofessional collaborative practice among qualified health practitioners to the involvement of pre-qualifying students in practicing interprofessional education. It is essential to establish outcome measures to enhance the seamless integration of interprofessional education and collaborative practice. The aim of this study was to develop a culturally appropriate quality measure for assessing interprofessional education and collaborative practice for health practitioners and students in Indonesia by performing cross-cultural validation of the collaborative practice assessment tool (CPAT). The consensus-based standards for the selection of health measurement instruments (COSMIN) standards of psychometric properties were used to guide the study. The evaluation of the psychometric properties was conducted, involving meticulous structural validity evaluation based on a three-step factorial analysis (exploratory factor analysis, confirmatory factor analysis, and multi-group confirmatory factor analysis) and measurement invariance. The parameters analyzed were related to the design requirements of a measure (i.e., targeted population, study sample, and size), the internal structure (structural validity, internal consistency, and measurement invariances), and hypotheses testing for construct validity based on a validated conceptual framework. This study involved 266 practitioners and 232 students. The COSMIN standards for general design requirements were fulfilled. Structural validity confirmed the 7-factor of 48-item structure; measurement invariances indicated configural, metric, and scalar invariants in both practitioner and student cohorts. Construct validity was confirmed by meeting the COSMIN requirement, with over 75% of the tested hypotheses accepted. In conclusion, the findings suggest the newly validated Indonesian CPAT has good psychometric properties concerning internal structure (i.e., structural validity, internal consistency, and measurement invariance) and hypotheses testing, and is therefore a quality measure for assessing interprofessional education and collaborative practice with health practitioners and students in Indonesia.